En Algérie "du temps de la France" ; (1950 - 1955) - Galland, Jean (Ed. Tirésias, 1998)
A fictionalized account of the author's experiences as a teacher in Algeria, 1950-1955.
Keywords: Geschichte 1950-1955; Algerien; Algeria -- Fiction; Erlebnisbericht